Implementasi Total Quality Management (TQM) di SMP Negeri 1 Dlanggu Kabupaten Mojokerto - Nawawi, Syu'aib (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
TQM should be applied to every Islamic education unit in order to encourage the quality of excellent service to stakeholders. Because, in today's sharp world of global competition, many people talk about